Development of a Sandwich Coil and LCC Converter-Based Wireless Charging System for Intelligent Electric Vehicles (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Wireless power transfer (WPT) is becoming the dominant method for charging electric cars, yet there is currently no equitable method for quantifying the power transfer. This article presents the Faraday coil transfer-power measurement (FC-TPM). FC-TPM utilizes sensor coils that do not make physical contact and are not connected to a circuit in order to measure the electromagnetic field generated by WPT. It then calculates the actual power that is sent across the space between the transmitter and reception coils. The measured quantity is the actual electromagnetic power, which represents the direct distribution of energy that clearly distinguishes the losses on both sides. The FC-TPM exhibited a hardware accuracy of 0.1% when tested with a 1-kW WPT system across a Rx coil sandwich with a maximum distance of 10 cm. Equitable metering encourages enterprises and people to adopt energy-conserving decisions and promote technological advancements by offering comprehensive information and accurately allocating cost burdens. This article is complemented by a film that emphasizes the crucial contributions made by this article.